THE EFFECT OF LOCUS OF CONTROL (LOC) ON IMPROVING STUDENT LEARNING OUTCOMES - Ahmad, Ikhsan Ibrahim; Hanifah, Nurdinah; Nugraha, Dadan (PD PGMI se Indonesia, 2023)
The study aims to determine the effect of LoC on improving social studies learning outcomes using quasi-experimental research with time series design. This research uses a quantitative approach with a quasi-experimental method. The population was all 5th grade students of SDN Penjaringan 08 Pagi & Penjaringan 01 and the sample was students of class VB of SDN Penjaringan 08 Pagi. In addition, the instruments used to measure learning outcomes were multiple choice & Likert scale for LoC. This research revealed three findings as follows: 1) The students' external & internal LoC values are 61.7% & 72.6%; 2) Based on the analysis of service quality variables, the t value (5.155) > t table (2.043) & sig value (0.000) < 0.05 with the regression coefficient value = 0.329, internal LoC variables on improving learning outcomes and the t value (3.847) > t table (2, 043) and sig value (0.001) < 0.05 with regression coefficient = 0.253 & based on one lane ANOVA test, sig value = 0.000 < 0.05, it is concluded that there is a significant influence & simultaneously and together internal & external LoC on improving social studies learning outcomes; 3) Based on the results of SPSS analysis, R = 0.748. So, this value explains the relationship between internal and external LoC on improving learning outcomes is very strong, significant, and positive and Adjusted R square = 0.527. This value is interpreted that all LoC contribute 52.7% to improving social studies learning outcomes.